Investment Plan Analysis To Increase Coal Production In PT Bukit Asam Tbk, Kabupaten Muara Enim, Sumatra Selatan - Wahyudi, Ichsan; Hasjim, Mahmud; Yusuf, Maulana (Management Analysis Journal, 2021)
Along with increasing economic growth, population, and growing industry, the demand for energy continues to increase. One of the alternative energy sources that increasingly exist with higher prices is coal. The area of ​​Muara Enim Regency has the prospect of coal mining commodities which are widespread. In this case, PT. Bukit Asam, Tbk will increase coal production by conducting a comprehensive investment planning analysis. Cost Present Value (CPV) and Benefit Cost Ratio (BCR) are the methods that will be used in this research. This study will also compare between investment and equipment rental to see the costs incurred. The data used is divided into two, namely primary data consisting of cashflow data, annual operational cost plans, prices of main and supporting equipment, bank interest rates, and effective working hours. While the secondary data consists of the condition and situation of the mining location. Based on the calculation results show that investment planning has a lower cost calculation than equipment rental. Benefit Cost Ratio (BCR) generated in this study is 1.935743906.